2021
DOI: 10.1136/bmjopen-2020-046829
|View full text |Cite
|
Sign up to set email alerts
|

Maternal emotional and physical intimate partner violence and early child development: investigating mediators in a cross-sectional study in a South African birth cohort

Abstract: ObjectivesThis study investigated associations between recent maternal intimate partner violence (IPV) (emotional, physical and sexual) and child development at 2 years as well as whether maternal depression or alcohol use mediated these relationships.DesignCross-sectional study nested in a South African birth cohort.SettingTwo primary care clinics in Paarl, South Africa.Participants626 mother–child pairs; inclusion criteria for maternal antenatal enrolment were clinic attendance and remaining in the study are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…A large body of evidence has further revealed that the detrimental impact of IPV against mothers could also extend to the next generation, leading to delayed development, poorer physical health, and more psychosocial problems in their children (8)(9)(10). For example, a cross-sectional study conducted in South Africa has found that children with maternal report of IPV were more likely to fall behind their peers in cognitive and language development (8). Longitudinal studies have also suggested that children of mothers with IPV exposure were at higher risk of both physical and psychological health problems, including asthma, and posttraumatic stress disorder (9,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of evidence has further revealed that the detrimental impact of IPV against mothers could also extend to the next generation, leading to delayed development, poorer physical health, and more psychosocial problems in their children (8)(9)(10). For example, a cross-sectional study conducted in South Africa has found that children with maternal report of IPV were more likely to fall behind their peers in cognitive and language development (8). Longitudinal studies have also suggested that children of mothers with IPV exposure were at higher risk of both physical and psychological health problems, including asthma, and posttraumatic stress disorder (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-accepted that women who had experienced IPV were at higher risk of both mental and physical impairment, as well as premature death ( 4 7 ). A large body of evidence has further revealed that the detrimental impact of IPV against mothers could also extend to the next generation, leading to delayed development, poorer physical health, and more psychosocial problems in their children ( 8 10 ). For example, a cross-sectional study conducted in South Africa has found that children with maternal report of IPV were more likely to fall behind their peers in cognitive and language development ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature demonstrated that IPV in man-dominant societies could interfere with women’s ability to meet basic reproductive needs and could harm the health of newborns and living children (Bair-Merritt et al, 2006; Barnett et al, 2021; Silverman et al, 2006b). Several parameters, such as child immunization and exclusive breastfeeding, could be influenced by IPV, and the mothers who experience IPV may not be able to fully meet the nutritional and developmental needs of the newborn; thus, this could compromise the health of the child and lead to irreversible adverse outcomes and long-term morbidities and even death (Ariyo & Jiang, 2021; Bair-Merritt et al, 2006; Silverman et al, 2006a).…”
Section: Discussionmentioning
confidence: 99%
“…Relationships with offspring and offspring outcomes. Of the 54 articles pertinent to associations between impaired internal working models and early parent-child relationships and offspring outcomes, 14,59,62,63,71,72,76,77,92,[107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][126][127][128][129][130]134,139,147,156,[165][166][167][168][169][170][171][172][173][174][175][176][177]…”
Section: Perinatal Substance Use and Impaired Internal Working Modelsmentioning
confidence: 99%
“…76,77,134,147,168 Approximately two-thirds of these pertinent studies addressed motherinfant relationships and one-third addressed mother-toddler relationships, reporting decreased maternal sensitivity, 59,92,166,167,169,172,177,178 more neutral maternal affect, 178 lower structuring and higher intrusiveness, 170 more harsh parenting, 170,179 higher maternal rigidity, 174 lower reflective function, 77 and high rates of parent-child separation. 134 Of the articles relevant to relational and child outcomes which reported on substance use, four addressed offspring outcomes, 62,147,171,175 with two reporting on child socioemotional development, 62,171 one reporting on child temperament, 147 and another reporting on child internalizing symptoms. 175 Given study heterogeneity and the low number of studies, it is difficult to make definitive conclusions, though one longitudinal study reported that prenatal substance use mediated the relationship between maternal childhood maltreatment experiences and young child internalizing symptoms.…”
Section: Perinatal Substance Use and Impaired Internal Working Modelsmentioning
confidence: 99%